HYPERTHERMIC INTRATHORACIC CHEMOTHERAPY (HITHOC) - A TERTIARY ONCOLOGICAL CENTER EXPERIENCE - Stojiljkovic, Dejan; Mitrovic, Sanja; Cvetkovic, Ana; Cvetic, Vladimir; Aleksic, Ana; Stojiljkovic, Tanja; Spuric, Igor (Medical Research, 2025)
Introduction: This study aimed to present our experience with HITHOC in the field of multimodality treatment of heterogeneous, potentially resectable, chemotherapy-sensitive pleural malignancies—primary and metastatic—limited to the unilateral thoracic inlet.Methods: The research included all patients who underwent a HITHOC procedure with CRS at the Institute for Oncology and Radiology of Serbia from January 2018 to December 2024. The indications for procedure were: resectable chemo-sensitive primary or residual/recurrent thoracic malignancies confined to one side of the thorax, and various metastatic diseases restricted to the unilateral thoracic inlet with achieved local disease control. HITHOC was performed with cisplatin (100 mg/m2 in 1000 ml of 5 % glucose, gradually heated to 42 °C) perfusion lasting 90 minutes. Results: Eleven patients were included in the study, with a mean age of 48.27 ± 18.37 years. The most common tumor pathology was thymoma, followed by malignant pleural tumors. Other tumor pathologies included ovarian cancer, Ewing's sarcoma, alveolar rhabdomyosarcoma, and lung cancer. Average follow-up was 41,73 (median: 35; range: 2-72) months. The overall survival rate was 64%. Conclusion: HITHOC procedure can be regarded as a safe, feasible, and effective approach for well-selected patients. It could be beneficial not only for its current indications, but also for chemosensitive pleural malignancies, both primary and metastatic, limited to the unilateral thoracic inlet.
Keywords: HITHOC; Hyperthermic intrathoracic chemotherapy; Pleural malignancies; Indications; Survival